Nationalizing crisis: the political economy of public policy in contemporary India - Nayak, Bhabani Shankar (ed.) (New Delhi, 2007)
The present book intends to make an innovative contribution to key debates in the burgeoning field of society, economy and politics in contemporary India. The arguments herein move beyond the traditional analysis of "cause and effect" relationships while addressing "crises" in its different forms. The study tries to map out the crises which are reinforced by the ruling class in India since decades in the process of identity formations based on race, religion, caste and culture in politics and dismantling the role of state in economy through the process of market led reforms. The crisis is again reinforced by the given political economy of the Indian society where masses have to sacrifice their development for the pleasure of others. Instead of solving these acute problems, the Indian ruling class tries to overcome it by diverting people from the real life issues through the process of spreading the venom of communalism and other emotive issues. The society and culture is being shaped by the economy, and economics does not lead politics rather it follows politics. Thus, it is necessary precondition to shape politics for the better economy that works for the masses. Apart from the market based advocacy, the ruling class in India also advocates for the technology and information. Of course, we need technology but till now it is in the hands of the few and far away from the masses. An understanding about crises and its reinforcing agencies will be essential for all future struggles for alternatives. While the students and teachers concerned with Development Studies will find this book informative, the general readers will find it a real eye-opener.
Keywords: Economics